Numerical Study on the Transient Thermal Performance of a Two-Phase Closed Thermosyphon - Zhongchao Zhao; Yong Zhang; Yanrui Zhang; Yimeng Zhou; Hao Hu (Energies, 2018)
The transient thermal performance of phase change and heat and mass transfer in a two-phase closed thermosyphon are studied with computational fluid dynamics (CFD). A CFD model based on the volume of fluid technique is built. Deionized water is specified as the working fluid of this thermosyphon. The CFD model reproduces evaporation and condensation in the thermosyphon at different heating inputs. The average wall temperatures are also analyzed. Variations of average wall temperatures indicate that this thermosyphon reaches a steady state after 19 s, and starts to work in advance when the heating input increases. Moreover, thermal resistance is decreased until a minimum (0.552 K/W) by increasing the heating input, and the effective thermal conductivity is elevated to a maximum (2.07 × 106 W/m∙K).